Energy Efficient Cooperation with Chip-Interleaved Transceivers in WSNs Over Frequency-Selective Fading Channels - Tian, Jianjie; Berber, Stevan; Rowe, Gerard (Wireless personal communications, 2017)
Cooperative diversity techniques have been utilized to improve the energy efficiency of wireless sensor networks (WSNs) operating over flat fading channels in a considerable number of literature. However, wireless channels of WSNs operating in indoor environments are supposed to be characterised by frequency-selective fading. Theoretical analysis of energy efficient cooperative communications in WSNs operating in indoor environments are rarely addressed. Therefore, this paper studies the energy efficient cooperative communications in WSNs operating over frequency-selective fading channels. Closed-form bit error rate expressions are derived for systems over frequency-selective fading channels. In order to fully explore the energy conservation potential of cooperative communications, solutions of the optimal transmit power allocation and the partner node selection are provided. Moreover, it is proven that the communication quality can be greatly improved by using chip-interleaving techniques in WSNs subject to flat fading channels. Thus, this paper investigates the energy-saving potential of chip-interleaved transceivers in WSNs subject to frequency-selective fading. Numerical results show that significant energy savings can be achieved via cooperations with chip-interleaved transceivers in WSNs operating in indoor environments.